ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI CASH HOLDING PERUSAHAAN MANUFAKTUR TAHUN 2017-2020 - Kevin Aldri; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2023)
This research aims to obtain empirical evidence on the influence of financial leverage, net working capital, firm size, profitability, growth opportunity, and capital expenditure on corporate cash holding in the manufacturing industry listed on the Indonesia Stock Exchange (IDX) during the period 2017-2020. This study used purposive sampling methods in sampling and obtained as many as 58 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2020. The study used multiple linear regression analysis. This research conducted data processing using Eviews application version 12 and Microsoft Excel 2019. The results of this study showed that financial leverage, net working capital, and capital expenditure negatively affect cash holding, profitability has a positive effect on cash holding, and firm size and growth opportunity have no effect on cash holding.